2015
DOI: 10.1177/0022034515581643
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Analyses of Skeletal Variation in Malocclusion

Abstract: This study evaluated associations between craniofacial candidate genes and skeletal variation in patients with malocclusion. Lateral cephalometric radiographs of 269 untreated adults with skeletal classes I, II, and III malocclusion were digitized with 14 landmarks. Twodimensional coordinates were analyzed using Procrustes fit and principal component (PC) analysis to generate continuous malocclusion phenotypes. Skeletal class classifications (I, II, or III) were used as a categorical phenotype. Individuals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 39 publications
2
102
0
9
Order By: Relevance
“…12,13 In an effort to address some of these knowledge gaps, a recent genetic association study of 71 craniofacial genes/loci in white subjects with severe malocclusion used both categorical (skeletal Class II or Class III vs Class I) and quantitative skeletal malocclusion phenotypes derived from cephalometric tracings and geometric morphometrics methods, respectively. 14 This study showed that the risk for skeletal Class II relative to Class I was modulated by rare alleles in variants near FGFR2 and EDN1 , whereas Class III risk was modulated by variants in FGFR2, COL1A1 , and TBX5 . In addition, SNPs near SNAI3 were highly associated with skeletal variations ranging from severely concave to convex skeletal profiles and SNPs near TWIST1 were associated with variations ranging from a large to a short mandibular body.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…12,13 In an effort to address some of these knowledge gaps, a recent genetic association study of 71 craniofacial genes/loci in white subjects with severe malocclusion used both categorical (skeletal Class II or Class III vs Class I) and quantitative skeletal malocclusion phenotypes derived from cephalometric tracings and geometric morphometrics methods, respectively. 14 This study showed that the risk for skeletal Class II relative to Class I was modulated by rare alleles in variants near FGFR2 and EDN1 , whereas Class III risk was modulated by variants in FGFR2, COL1A1 , and TBX5 . In addition, SNPs near SNAI3 were highly associated with skeletal variations ranging from severely concave to convex skeletal profiles and SNPs near TWIST1 were associated with variations ranging from a large to a short mandibular body.…”
mentioning
confidence: 73%
“…A sample of 300 untreated healthy subjects (average age, 29.9 years; age range, 12–68 years) seeking orthodontic treatment at the Department of Orthodontics of the University of Iowa was recruited and classified into skeletal Class I (n = 63), Class II (n = 154), or Class III (n = 83) according to criteria specified previously 14 and shown in Supplemental Figure 1. Of these, about 80% were white (n = 239), and the remaining subjects had other ancestries (Table I).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This facilitates the examination of morphology in terms of shape variation without the confounding influence of size. In biology, shape variation is often used as a morphological proxy for genetic variation, and the interplay between genes and morphology has served as the basis for numerous studies of genotype vs. phenotype interactions in many different biological systems (Debat and David, 2001; Klingenberg et al, 2001; Workman et al, 2002; Klingenberg et al, 2004; Miller et al, 2014; da Fontoura et al, 2015). Typically, studies of morphological variation in bilaterally symmetric structures (such as the dental arches) address both aspects of symmetric and asymmetric shape variation.…”
Section: Introductionmentioning
confidence: 99%